Juxtaposition of the images of Jagiello and Sigismund in the poem «The Prussian War»: continuity, prototype, myth-making - Yafimau, Aliaksandr V. (Journal of the Belarusian State University. Philology, 2019)
On the basis of today’s interdisciplinary approaches considered juxtaposition images Jagiello and Sigismund in the poem of Joannis Vislicensis «The Prussian War». It is hypothesized that Jagiello is indicated not only the comments as an independent character, but also as a type of his offspring, and his biography contains some predictions about what will be (should be) Sigismund’s biography. It draws attention to the characteristic of the Renaissance myth-making in the poem.